Beginning Linux system administration : LiveLessons - Vugt, Sander van; Safari eBooks ([Place of publication not identified] : Prentice Hall : Pearson, 2016)
"Learn solid fundamental Linux operating system skills with Beginning Linux System Administration LiveLessons. Taught by best-selling author and trainer Sander van Vugt, Beginning Linux System Administration LiveLessons walks you through the essential system administration tasks so you can up and running in Linux quickly. This video course consists of 12 lessons. You will start with the basics, from determining which distribution is right for you to walking through the steps of installing Linux on the two most popular flavors: Ubuntu and Red Hat. You will then connect to Linux. You will then get a chance to really get your feet wet, using an editor and working with files. You will then dive into managing permissions, processes and software before working with logs, exploring Linux security and finally managing services. The author uses real world examples throughout and focuses on teaching you how to operate and manage some of the most frequently used Linux services. This course also provides information on how Linux administration is typically dealt with in corporate environments, with a focus on content management systems, automatic deployment systems and operating Linux from the cloud."--Resource description page.
Presenter, Sander van Vugt.
Title from title screen (viewed May 18, 2016).
Keywords: Linux; UNIX (Computer file); Operating systems (Computers) -- Automation; Electronic books